2021
DOI: 10.1097/scs.0000000000007795
|View full text |Cite
|
Sign up to set email alerts
|

The Ideal Nasal Tip Projection and Rotation Angles in Chinese: A Preference Analysis of the General Population

Abstract: Rhinoplasty to reshape the nasal tip is increasingly popular among Chinese women. Aesthetic standards vary across different ethnic groups and it is key to identify preferences for the ideal nasal tip in China to set surgical goals. Therefore, we administered an online survey to plastic surgeons and the public through social media to rank nasal tip images by aesthetic preference. Images were created from a single photograph to show various dimensions of nasal tip projection to nasal dorsum length ratio (NTP/NDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In addition, we studied the absolute value of nasion parameters instead of the ratio between nasion and tip projection. This is based on our previous study about ideal nasal tip aesthetics, in which we found Chinese overwhelming preferences of nasal tip projection to nasal dorsum length ratio was 0.63, and nasal rotation angle was 106 degrees 10. Therefore, we modified the standardized photograph according to ideal nasal tip parameters at the beginning of the study and investigated different nasion parameters while keeping the nasal tip constant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we studied the absolute value of nasion parameters instead of the ratio between nasion and tip projection. This is based on our previous study about ideal nasal tip aesthetics, in which we found Chinese overwhelming preferences of nasal tip projection to nasal dorsum length ratio was 0.63, and nasal rotation angle was 106 degrees 10. Therefore, we modified the standardized photograph according to ideal nasal tip parameters at the beginning of the study and investigated different nasion parameters while keeping the nasal tip constant.…”
Section: Discussionmentioning
confidence: 99%
“…Images were modified using Adobe Photoshop (Adobe Systems Inc., San Jose, CA) to create different nasal parameters. First, we modified nasal tip parameters to ideal Chinese nasal tip projection and rotation according to our previous study 10. After the nasal tip aesthetics were determined, we measured the height of nasion and forehead from the plane of medial canthus (Fig.…”
Section: Methodsmentioning
confidence: 99%